Morfometric characteristics, pedology and land use with special consideration on viticulture and fruit growing in the Slovenske gorice region between the Mura and Pesnica rivers - Marič, Martin (Journal for Geography, 2017)
When mentioning The Slovenske gorice region an average Slovene resident thinks of hills with vineyards and orchards. However, the appearance of this region between the Mura and Pesnica Rivers has changed. The number of vineyards and orchards has reduced over the years. In this article, we analyzed the links between natural factors and land use. The focus was on the impact of relief, bedrock, and soil types on viticulture and fruit farming. Considering the natural factors, we analyzed where else is also possible and the most advantageous to grow vineyards and orchards. Those could, in association to appropriate social factors, add a large value to the agriculture in northeastern Slovenia.
Keywords: viticulture; fruit farming; relative height; aspects; slopes; global solar irradiance; bedrock; soil types